Evaluating Salivary Apelin Level among Chronic Periodontitis Patients, with and without Type 2 Diabetes Mellitus utilizing Enzyme‑Linked Immunosorbent Assay: A Comparative Study - Hirani, Tanvi; Haq, Md Ahsanul; Shetty, Neetha J; Patel, Viral; Ahmad, Rahnuma; Sinha, Susmita; Dutta, Siddhartha; Haque, Mainul; Kumar, Santosh (Bangladesh Journal of Medical Science, 2023)
Background: Periodontitis is a chronic inflammatory disorder mainly due to a decrease in the immune system caused by periodontal pathogens. The relationship of apelin among chronic generalized periodontitis (CGP) and type 2 diabetes mellitus (T2DM) has been reported. This study intends to assess the level of apelin in saliva from patients of healthy individuals, individuals with CGP, and CGP + T2DM, and evaluate the role of apelin adipokine in inflammation and insulin resistance. New treatment modalities can be invented using apelin in host modulation therapies. Methods: The study comprised 300 patients that were enrolled according to their clinical findings and were divided into three groups chronic periodontitis (n=100), chronic periodontitis with T2DM (n=100), and healthy controls (n=100). Probing pocket depth (PPD), clinical attachment level (CAL), and salivary Apelin (AP) were obtained. With the help of the enzyme-linked immunosorbent assay (ELISA) kit, the salivary apelin level was measured. A statistical software package was used for the surveying of collected data. Results: Group three[CGP+DM] shows the highest salivary apelin level compared to CGP patients without DM. It was 15.43±2.05ng/dl in CGP and 24.08 ± 3.60ng/dl in CGP with DM. All three groups found a statistically significant difference in mean Apelin Level, PPD, and CAL. Conclusion: This study indicated a possible role of adipokines in inflammation and glucose level regulation in patients with T2DM and CGP. In the coming era, apelin levels in saliva can be used for screening objectives in large populations to assure the risk of destructive periodontal disease. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 305-315